Lip Repositioning Surgery: A Simple Smile and Life Transformation Procedure - Besir Salihu; Zana Agani; Arta Sinanaj Demiri (Case Reports in Dentistry)
Excessive display of the gums when smiling, known as gummy smiles, can lead to aesthetic concerns and emotional discomfort for individuals. In recent times, there has been a notable rise in the popularity of gummy smile surgery as a cosmetic procedure aimed at addressing this problem. A novel technique known as lip repositioning has emerged and gained recent popularity, either on its own or in conjunction with other approaches. In specific situations, it offers a simpler, less intricate alternative to more extensive surgical procedures, resulting in a pleasing and satisfactory camouflage effect while reducing postoperative complications. This case report illustrates the effective treatment of a gummy smile in a patient with excessive gum exposure using a lip repositioning technique. The procedure involved the removal of a partial thickness strip of mucosa lining in the maxillary buccal vestibule, without including the labial frenulum, and suturing the lip lining to the gum line. Our aim was to present lip repositioning as an effective method for reducing excessive gum exposure and addressing any unevenness in a minimally invasive manner. We sought a solution that offers long-lasting results over time while minimizing the chances of the issue recurring, with a 14-month follow-up.